2015
DOI: 10.1016/j.fertnstert.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl substances and ovarian hormone concentrations in naturally cycling women

Abstract: Objective To examine associations between environmental exposure to perfluoroalkyl substances (PFASs) and ovarian hormone concentrations in naturally cycling women. Design Estradiol and progesterone were measured in saliva samples collected daily for a single menstrual cycle and concentrations of PFASs (including perfluoroctane sulfonate [PFOS] and perfluoroctanoic acid [PFOA]) were measured in serum samples collected during the same cycle. Setting Tromsø, Norway. Patients 178 healthy, naturally cycling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 106 publications
5
44
2
Order By: Relevance
“…PFOS can inhibit the secretion of progesterone in a concentration-dependent manner in human placental syncytiotrophoblasts (Zhang et al 2015). Barrett et al (2015) reported a negative association between serum PFOS exposure (but not PFOA) and saliva progesterone levels in healthy nulliparous women 25–35 years of age. In addition, we reported that prenatal exposure to PFOS was inversely associated with progesterone levels in cord blood of male and female infants in the same cohort.…”
Section: Discussionmentioning
confidence: 95%
“…PFOS can inhibit the secretion of progesterone in a concentration-dependent manner in human placental syncytiotrophoblasts (Zhang et al 2015). Barrett et al (2015) reported a negative association between serum PFOS exposure (but not PFOA) and saliva progesterone levels in healthy nulliparous women 25–35 years of age. In addition, we reported that prenatal exposure to PFOS was inversely associated with progesterone levels in cord blood of male and female infants in the same cohort.…”
Section: Discussionmentioning
confidence: 95%
“…In nulliparous women Barrett et al (2015) found that higher PFOS and to some extent PFOSA were associated with lower levels of estradiol and progesterone. PFOA, PFNA, PFDA, PFUnA and PFHxS were not clearly associated with either hormone, and the associations in parous women were inconsistent.…”
Section: Reproductive Hormonesmentioning
confidence: 92%
“…For semen volume, total sperm count and sperm concentration, none of the studies found consistent associations with exposure to any PFASs (PFOA, PFOS, PFHxS, PFHpS, PFNA, PFDA, PFOSA, Et-PFOSA-AcOH, Me-PFOSA-AcOH), and there were no tendencies for the estimates to point in the same direction (Joensen et al 2009;Raymer et al 2012;Toft et al 2012;Joensen et al 2013; Barrett et al 2015;Buck Louis et al 2015;Den Hond et al 2015) (see Table 3). PFOA exposure was associated with a higher percentage of motile sperm in the study by Toft et al (2012).…”
Section: Semen Characteristicsmentioning
confidence: 95%
See 2 more Smart Citations